The Relationship Between Knowledge Level and Dietary Compliance with Blood Glucose Levels in Patients with Type II Diabetes Mellitus - Edarni Zebua; Melva Hartati Jesika Hutasoit; Salmi Angraini; Dian Novita; Siti Aisyah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Diabetes mellitus is a metabolic disease characterized by elevated blood glucose levels, with type II diabetes mellitus contributing the majority of cases due to unhealthy dietary patterns, low levels of knowledge, and poor adherence in disease management. Proper dietary management is essential to control blood glucose levels and prevent complications. This study aimed to determine the relationship between the level of knowledge and dietary adherence with blood glucose levels among patients with type II diabetes mellitus in the inpatient ward of RSUD Tarutung. This study used a quantitative method with an analytic approach and a cross-sectional design. The population consisted of 54 patients, and total sampling was applied. Data were collected using a questionnaire and analyzed using the Spearman correlation test. The results show that there is a significant relationship between knowledge level and blood glucose levels (p=0.000; r=-0.598) as well as between dietary adherence and blood glucose levels (p=0.001; r=-0.434). Both variables show moderate negative correlations, indicating that better knowledge and higher dietary adherence are associated with better-controlled blood glucose levels. In conclusion, knowledge and dietary adherence play an important role in controlling blood glucose levels among patients with type II diabetes mellitus. It is recommended that health professionals enhance patient education and that future researchers examine other factors influencing blood glucose levels using more diverse research designs.